Aerodynamic Characteristics of a Micro Multi-Rotor Aircraft with 12 Rotors Considering the Horizontal Wind Disturbance - Yao Lei; Wenjie Yang; Hengda Wang (Applied Sciences, 2020)
Wind disturbance posed difficulties for the stability of the micro air vehicles (MAVs) with attitude variation. In this paper, the aerodynamic performance of a MAV with six coaxial rotor pairs considering the horizontal wind is investigated by both experiments and numerical simulations. First, the effect of the horizontal wind on the multi-rotor aircraft is analyzed in detail. Then, low-speed wind tunnel tests were performed to obtain the thrust and power consumption and the aerodynamic performance of the multi-rotor aircraft (l/D = 1.2 and h/D = 0.19) with the rotational speed of 1500–2300 r/min in the horizontal wind ranged from 0 to 5 m/s. Finally, the distribution of streamline, the pressure of the blade tip, and the velocity and the vortices in the flow field of a multi-rotor aircraft with horizontal wind disturbance, were simulated and studied using the computational fluid dynamics (CFD) method. Through the comparison of experimental results and simulation results, it can be seen that the horizontal wind disturbance will increase power consumption to weaken the aerodynamic performance at higher rotor speeds. However, larger thrust and better hover performance are obtained at lower rotational speeds with good wind resistance. Additionally, due to the mutual induction between rotor wakes, the interactions of downwash flows become more intense at higher rotational speeds or larger wind speeds where the vortexes at the blade tip deformed and moved along with the wind.